Anxiety of Cuban Dentistry students and intention to abandon studies during the COVID-19 pandemic - Chaple Gil, Alain Manuel (2021)
ABSTRACT Objective: to determine the prevalence of anxiety in stomatology students during the COVID-19 pandemic and its relationship with the intention to leave their study programs. Methods: descriptive-cross-sectional study where an online survey was applied to assess the mental health of stomatology students and residents and the intention to abandon their studies during COVID-19. 917 students from 16 provinces responded. A 24-item survey was made on intentions to leave the study programs both in undergraduate students and residents of specialties, general mental health from the point of view of anxiety and effects of the COVID-19 Pandemic. The generalized anxiety disorder scale was used to determine anxiety. The variables necessary to carry out the analyzes were dichotomized and the bivariate relationships between the intention to abandon the study programs and each predictor were evaluated by generating Odds Ratio as a measure of effect size. Independence tests were performed to identify differences in proportions with a 95% confidence interval (CI). Results: 37.4% of the students had Generalized Anxiety Disorder. The need for libraries (1.92 [1.34; 2.74]; <0.001), virtual libraries (2.19 [1.66; 2.89]; <0.001), tutoring services (3.26 [2.47; 4.32]; 0.000), digital books (1.65 [1.26 ; 2.17]; <0.001) and other needs (1.70 [1.06; 2.75]; 0.029). Anxiety was related to the intention to abandon their careers (3.05 [2.01; 4.69]; p <0.001) and the same as the perception of whether the COVID-19 pandemic had negatively impacted their mental health (1.87 [1.20; 2.99] The logistic regression showed significance reaffirming the results. Conclusions: More than a quarter of the participants had generalized anxiety disorder. The desire to abandon their study programs by the participants was related to the presence of anxiety and their self-perception that the COVID-19 pandemic has impacted on their mental health.